Audiovisual Interactions in Front and Rear Space - Montagne, Christopher; Zhou, Yi (Frontiers in Psychology, 2018)
The human visual and auditory systems do not encode an entirely overlapped space when static head and body position are maintained. While visual capture of sound source location in the frontal field is known to be immediate and direct, visual influence in the rear auditory space behind the subject remains under-studied. In this study we investigated the influence of presenting frontal LED flashes on the perceived location of a phantom sound source generated using time-delay-based stereophony. Our results show that frontal visual stimuli affected auditory localization in two different ways – (1) auditory responses were laterally shifted (left or right) toward the location of the light stimulus and (2) auditory responses were more often in the frontal field. The observed visual effects do not adhere to the spatial rule of multisensory interaction with regard to the physical proximity of cues. Instead, the influence of visual cues interacted closely with front–back confusions in auditory localization. In particular, visually induced shift along the left–right direction occurred most often when an auditory stimulus was localized in the same (frontal) field as the light stimulus, even when the actual sound sources were presented from behind a subject. Increasing stimulus duration (from 15-ms to 50-ms) significantly mitigated the rates of front–back confusion and the associated effects of visual stimuli. These findings suggest that concurrent visual stimulation elicits a strong frontal bias in auditory localization and confirm that temporal integration plays an important role in decreasing front–back errors under conditions requiring multisensory spatial processing.